Accounting education quality and accounting job performance: An employer perspective in Sri Lanka - Peemanee, Jindarat; Weerarathna, Ranitha; Madhavika, Naduni; Kumarapperuma, Chathurini (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to investigate, from the viewpoint of employers, how the caliber of accounting education impacts the job performance of accounting graduates in Sri Lanka. A total of five criteria were employed to assess the quality of accounting education: communication skills, ethical standards, digital competencies, foundational accounting knowledge, and adaptability. The research involved administering a questionnaire to finance managers linked to firms on the Colombo Stock Exchange, with the findings interpreted via multiple regression analysis. The findings revealed that while foundational accounting knowledge did not exhibit a significant effect on performance, digital competencies, ethical standards, communication skills, and adaptability did indeed have a notable impact. Findings show that to advance the readiness of graduates for labor opportunities in Sri Lanka, accounting programs should be framed around the enhancement of practical know-how and the establishment of synergies between industry players and academic institutions.